Preparation method of high-purity fibrous CsAg5Te3 nano-thermoelectric powder and thermoelectric block

Through microwave solvent thermal method and discharge plasma sintering technology, high-purity fiber-like CsAg5Te3 nano thermoelectric powder and dense thermoelectric blocks were prepared, solving the problems of complex processes, large energy consumption and uncontrollable products in the prior art, and achieving high-efficiency and low-energy consumption thermoelectric material preparation.

CN116639666BActive Publication Date: 2025-05-02CHANGZHOU UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310562499.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-18
Publication Date
2025-05-02
Estimated Expiration
2043-05-18

AI Technical Summary

Technical Problem

The existing CsAg5Te3 thermoelectric materials have complex preparation processes, long reaction time, large energy consumption, and uncontrollable product morphology, size and crystal purity.

Method used

The microwave solvent-thermal method was used to prepare high-purity fiber-like CsAg5Te3 nanothermal powders through gradient heating reactions, and dense thermoelectric blocks were prepared by discharge plasma sintering.

Benefits of technology

It achieves low reaction temperature, short time, low raw material price, high product purity and high density, avoids the problems of long reaction time and large energy consumption in traditional technology, and has high thermoelectric properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116639666B_ABST
    Figure CN116639666B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of the preparation of nano-thermoelectric materials, and specifically relates to a method for preparing high-purity fibrous CsAg5Te3 nano-thermoelectric powder and thermoelectric bulk. By combining microwave solvothermal method with gradient temperature rise, using inexpensive CsNO3, AgNO3, and Na2TeO3 as raw materials, the cost is greatly reduced and the purity is improved. The prepared CsAg5Te3 nano-material has a fibrous structure. Then, the prepared fibrous CsAg5Te3 powder is rapidly sintered into a dense thermoelectric bulk by using spark plasma sintering technology. The obtained thermoelectric bulk exhibits good thermoelectric properties. At 675K, the optimal thermoelectric figure of merit zT can reach 0.7. The present invention aims to solve the problems in the process of preparing thermoelectric materials by existing methods, such as high raw material cost, complex preparation process, long reaction time, large energy consumption, and uncontrollable morphology and size of the obtained products, and provides new ideas for the preparation of multi-component thermoelectric materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of nano thermoelectric material preparation, and specifically relates to a method for preparing a high-purity fibrous CsAg5Te3 nano thermoelectric powder and a thermoelectric block. Background Art

[0002] CsAg5Te3 is a new type of metal-rich chalcogenide (metal:chalcogen ratio of 6:3) with a unique tunnel structure. The compound has semiconductor properties and consists of a three-dimensional tunnel network (Ag5Te3) filled with Cs counterions. The network is quite complex. The complex crystal structure and large unit cell provide them with intrinsically low lattice thermal conductivity. In addition, CsAg5Te3 has a small band gap (0.65eV), small polar covalent bonds, and high carrier mobility, which gives it good electrical transport properties. Therefore, CsAg5Te3 has been confirmed to be a promising new thermoelectric material.

[0003] At present, there is very little research on CsAg5Te3 thermoelectric materials. One of the main reasons is that the preparation of CsAg5Te3 thermoelectric materials is quite complicated. So far, there are few reports on CsAg5Te3 materials. Among them, in 1995, Li et al. reported a method for preparing CsAg5Te3 powder (J.Solid State Chem.1995,218:1–4). They used a two-step method to first synthesize binary phase Cs2Te and then react with Ag to obtain the target product. The reaction temperature was as high as 600°C and the entire reaction process took 10 days. In 2014, Wu Liming et al. first reported the preparation of CsAg5Te3 thermoelectric block (Chinese Patent 105803532B, 2016,07,27). They used expensive high-purity Ag, Te and Cs2Te3 as raw materials, obtained CsAg5Te3 powder material by high-temperature solid phase method at 750-950℃ for 20-48h, and then obtained CsAg5Te3 thermoelectric block by hot pressing method at 400-500℃ for 30-90min. In 2016, Wu Liming and others reported the excellent thermoelectric performance of CsAg5Te3 again (Angew.Chem.Int.Ed.2016,55,1-7). Using high-purity Ag, Te and Cs2Te3 as raw materials, CsAg5Te3 thermoelectric materials were prepared by high-temperature solid-phase method. The whole process required a reaction at 800℃ for 2h, and then the prepared CsAg5Te3 powder was sintered into a thermoelectric block by spark plasma sintering technology. Although the preparation time was shortened, the raw materials were expensive, the high-temperature smelting process consumed a lot of energy, and the morphology and size of the obtained product were uncontrollable. Summary of the invention

[0004] On the one hand, the present invention aims to solve the problems of complex process, long reaction time, high energy consumption, uncontrollable product morphology, size and crystal purity in the process of preparing alloy thermoelectric materials in existing methods. The present invention provides a high-purity fibrous CsAg5Te3 nano-thermoelectric powder. The preparation method is a microwave solvent thermal method. The method is simple to operate, fast and efficient, and has low energy consumption. High-purity fibrous CsAg5Te3 nano-materials with regular morphology can be obtained under a gradient heating process, which provides the necessary conditions for obtaining high-purity and dense thermoelectric blocks, thereby ensuring higher thermoelectric performance.

[0005] The specific method includes the following steps:

[0006] CsNO3, AgNO3 and Na2TeO3 were weighed respectively according to the molar ratio of Cs:Ag:Te=12:5:3, dissolved in a transparent mixed solution containing ethylene glycol, NaOH and polyvinylpyrrolidone (PVP), and fully disturbed at room temperature to obtain a black solution; the black solution was transferred to a Teflon high-pressure reactor, and the reactor was placed in a microwave reactor for a gradient temperature increase reaction, the gradient temperature increase reaction was first heated to 120°C at a rate of 24°C / min, kept warm for 5 minutes, and then heated to 230°C at a rate of 22°C / min, and kept warm for 15 minutes. After the reaction was completed, the dark gray product was separated and purified to obtain the high-purity fibrous CsAg5Te3 nanomaterial.

[0007] Furthermore, the separation and purification method includes: washing the reaction product with deionized water and anhydrous ethanol by centrifugation for multiple times, the centrifuge speed is 8000rpm, and the centrifuged product is placed in a vacuum drying oven and dried at 60°C for 8h.

[0008] In another aspect, the present invention provides a method for preparing a thermoelectric block, comprising the following steps: subjecting the high-purity fibrous CsAg5Te3 nanopowder prepared according to the above method to spark plasma sintering, specifically, rapidly sintering at an axial pressure of 40 to 60 MPa and 400 to 500°C for 5 to 10 minutes to obtain a dense CsAg5Te3 thermoelectric block with a density of 6.5 to 7.1 g / cm -3 The relative density is as high as 93-97% (the theoretical density of CsAg5Te3 block is 7.07gcm -3 ).

[0009] Furthermore, the best thermoelectric performance was obtained under the conditions of spark plasma sintering at 450 °C and axial pressure of 50 MPa. At 675 K, the thermal conductivity was as low as 0.24 Wm -1 K -1 , conductivity can reach 47Scm -1 , Seebeck coefficient can reach 227μVK -1, the best thermoelectric figure of merit zT is 0.7.

[0010] The beneficial effects of the present invention are as follows:

[0011] (1) The microwave solvent thermal method provided by the present invention has low reaction temperature, short reaction time, low raw material price and high product yield, thus avoiding the problems of long reaction time and high energy consumption of traditional technology.

[0012] (2) The CsAg5Te3 nano-thermoelectric material prepared by the microwave method in combination with gradient heating has high purity and a regular nano-fibrous structure; the CsAg5Te3 thermoelectric block prepared by the spark plasma sintering method has a high degree of densification.

[0013] (3) The preparation method of the present invention has a certain universality and is suitable for preparing multi-element nanomaterials and thermoelectric blocks with complex structures. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 The schematic diagram of the microwave reaction preparation process of the CsAg5Te3 nanopowder of the present invention is as follows: (a) is a microwave reaction device, and (b) is a gradient temperature increase heating process curve during microwave reaction.

[0015] Figure 2 The following are the X-ray diffraction analysis patterns of the obtained CsAg5Te3 nanopowders: (a) is the X-ray diffraction pattern of the CsAg5Te3 powder obtained under the direct heating program, and (b) is the X-ray diffraction pattern of the CsAg5Te3 powder obtained under the gradient heating program.

[0016] Figure 3 The scanning electron microscope images of the obtained CsAg5Te3 nanopowders are as follows: (a) and (b) are the low-magnification and high-magnification SEM images of the CsAg5Te3 powders obtained by direct microwave heating reaction; (c) and (d) are the low-magnification and high-magnification SEM images of the CsAg5Te3 powders obtained by microwave gradient heating reaction.

[0017] Figure 4 X-ray diffraction analysis patterns of CsAg5Te3 thermoelectric blocks: (a) is the standard X-ray diffraction pattern of CsAg5Te3, and (b) is the X-ray diffraction pattern of the thermoelectric block 2 obtained by spark plasma sintering.

[0018] Figure 5 Scanning electron microscope images of the CsAg5Te3 thermoelectric block: (a) is a SEM image of the cross section of the CsAg5Te3 thermoelectric block 2 at low magnification, and (b) is a SEM image of the cross section of the thermoelectric block 2 at high magnification.

[0019] Figure 6Figure 3 shows the relationship between the thermal transport properties of the CsAg5Te3 thermoelectric bulk and temperature: (a) is the relationship between the thermal diffusion coefficient of the bulk sample and temperature, and (b) is the relationship between the thermal conductivity of the bulk sample and temperature.

[0020] Figure 7 The graphs show the relationship between the electrical transport properties of the CsAg5Te3 thermoelectric block 2 and temperature: (a) shows the relationship between the conductivity of the block 2 and the temperature, (b) shows the relationship between the Seebeck coefficient of the block 2 and the temperature, and (c) shows the relationship between the power factor of the block 2 and the temperature.

[0021] Figure 8 : is the relationship diagram of the thermoelectric figure of merit zT and temperature, a is the relationship between the thermoelectric figure of merit zT and temperature of the CsAg5Te3 thermoelectric block 2 in this experiment, and b is the thermoelectric figure of merit in the literature (Angew.Chem.Int.Ed.2016,55,1-7). DETAILED DESCRIPTION

[0022] The present invention is described in detail below by examples, but the protection scope of the present invention is not limited to the following examples.

[0023] In the embodiment, the microwave reaction device adopts CEM MARS 6 high-throughput closed microwave digestion instrument produced by CEM Corporation of the United States.

[0024] In the embodiment, the thermoelectric block sintering device adopts the SPS-211Lx spark plasma sintering furnace produced by Fuji Electronics Industry Co., Ltd. of Japan.

[0025] In the embodiments, the thermal conductivity is tested by using a LFA457 laser thermal conductivity tester manufactured by Netzsch of Germany; the electrical conductivity and Seebeck coefficient are measured by using a SBA458 thermoelectric performance tester manufactured by Netzsch of Germany.

[0026] The various commonly used chemical reagents used in the examples are all commercially available products, among which CsNO3, AgNO3 and Na2TeO3 have a purity of 99.9%.

[0027] Example 1 Preparation of fibrous CsAg5Te3 nanopowder

[0028] CsNO3 is used as a cesium source, AgNO3 is used as a silver source, Na2TeO3 is used as a tellurium source, ethylene glycol is used as a solvent, NaOH is used as a pH regulator, and PVP is used as a surfactant. Under microwave stimulation, CsAg5Te3 nanopowder with regular morphology is obtained by reaction. The method specifically comprises the following steps: 0.5g NaOH and 0.8g PVP are dissolved in 50ml ethylene glycol solution, and stirred thoroughly to obtain a colorless and uniform solution; 0.9355g CsNO3, 0.3397g AgNO3 and 0.2658g Na2TeO3 (controlling Cs:Ag:Te=12:5:3 (molar ratio) is a necessary condition for obtaining high-purity fibrous CsAg5Te3 nanomaterials in the present invention. Many other ratios have been tried in the experiment, but the target purity material has not been obtained), under room temperature, magnetically stirred at a speed of 500 rpm to obtain a black mixed solution; the above black mixed solution is transferred to a 100 ml Teflon high-pressure reactor, sealed and placed in a microwave reactor, and the gradient heating program is: heated to 120°C at a speed of 24°C / min under a power of 1800W, kept warm for 5 minutes, and then heated to 230°C at a speed of 22°C / min, and kept warm for 15 minutes; in order to verify the effectiveness of the gradient heating of microwave reaction, a direct heating comparison experiment was set up, that is, directly heated to 230°C at a speed of 23°C / min under the condition of 1800W, and kept warm for 15 minutes. After the reaction is completed, the products obtained by the above two heating procedures are cooled to room temperature, and then the obtained products are respectively loaded into centrifuge tubes, and are centrifuged and washed with deionized water and anhydrous ethanol for multiple times in turn. The products after centrifugation are placed in a vacuum drying oven and dried at 60°C for 8 hours to obtain powder samples.

[0029] The microwave reaction device selected in Example 1 is as follows Figure 1 As shown in (a), up to 12 Teflon high-pressure reactors with a volume of 100 ml can be placed in the microwave reaction furnace cavity at the same time. Figure 1 (b) is the gradient heating process curve of the microwave reaction.

[0030] The two powder samples obtained in Example 1 were subjected to X-ray diffraction analysis, and the results were as follows: Figure 2 shown. Figure 2(a) is the X-ray diffraction pattern of CsAg5Te3 powder obtained under the direct heating program, and (b) is the X-ray diffraction pattern of CsAg5Te3 powder obtained under the gradient heating program. Compared with the standard diffraction pattern of CsAg5Te3 (PDF#83-0130), it is found that the X-ray diffraction patterns of the experimentally prepared powders are highly consistent with the standard diffraction patterns of CsAg5Te3 powders, indicating that microwave reaction can prepare CsAg5Te3 powders. Careful observation shows that there are trace amounts of impurities in the powder prepared by the direct heating program. After searching, it is found that the impurity is Ag2Te (PDF#81-1985) phase, while there are no other impurities in the powder prepared by microwave gradient heating reaction, indicating that gradient heating helps the system to react completely, thereby obtaining high-purity CsAg5Te3 powder.

[0031] The morphology and structure of the two powder samples obtained in Example 1 were characterized. Figure 3 As shown, Figure 3 (a) and (b) are low-magnification and high-magnification SEM images of CsAg5Te3 powder obtained by microwave direct heating reaction. It can be seen from the figures that the powder obtained by direct heating reaction is a short rod-like structure and most of them are agglomerated together. Figure 3 (c) and (d) are the low-magnification and high-magnification SEM images of the CsAg5Te3 powder obtained by microwave gradient heating reaction. The CsAg5Te3 powder obtained at this time has a regular morphology. The high-magnification SEM results show that the CsAg5Te3 powder presents a regular nanofiber structure.

[0032] Example 2 Preparation of CsAg5Te3 Thermoelectric Block

[0033] 2.5 g of the CsAg5Te3 powder sample obtained by gradient heating in Example 1 is placed in a graphite mold dedicated to a spark plasma sintering furnace with a diameter of 12.7 mm, and the graphite mold filled with powder is placed in the spark plasma sintering furnace, the furnace chamber is evacuated to vacuum, the axial pressure is set to 40-60 MPa, the furnace temperature is 400-500°C, and the temperature is kept for 10 minutes. After the sintering is completed, it is naturally cooled to room temperature, and the block in the graphite mold is taken out to obtain a high-density disc-shaped block with a diameter of 12.7 mm and a thickness of 3 mm. Table 1 shows the spark plasma sintering temperature and pressure when preparing the CsAg5Te3 block sample, as well as the density and relative density of the obtained sample.

[0034] Table 1

[0035]

[0036] The thermoelectric block sample obtained in Example 2 was subjected to X-ray diffraction analysis, and the results are as follows: Figure 4 shown. Figure 4(a) is the standard diffraction pattern of CsAg5Te3 (PDF#83-0130), (b) is the X-ray diffraction pattern of bulk 2, and the diffraction peak positions and shapes of the XRD spectra of bulks 1, 3, 4, and 5 are similar to those of Figure 4 (b) is the same. It can be concluded that the X-ray diffraction pattern of the thermoelectric block is highly consistent with the standard diffraction pattern of CsAg5Te3, indicating that the fibrous CsAg5Te3 powder can still maintain its crystal structure after spark plasma sintering.

[0037] The morphology of the cross section of the block 2 sample obtained in Example 2 was characterized, and the results were as follows: Figure 5 shown. Figure 5 (a) is a SEM image of the cross section of the CsAg5Te3 thermoelectric block at low magnification. It can be seen that its structure is dense, indicating that spark plasma sintering can quickly prepare dense thermoelectric blocks. Figure 5 (b) is a SEM image of the cross-section of the thermoelectric block at high magnification. The results show that the CsAg5Te3 thermoelectric block contains flat nanosheets and dense granular structures, and the edges of the dense granular structure have lamellar textures. This is mainly because the high-temperature plasma in the high-temperature and high-pressure spark plasma sintering furnace of the fibrous CsAg5Te3 powder will quickly soften the surface of the fibrous CsAg5Te3 powder and bond it together with the adjacent powders, while the axial high pressure will cause the bonded powders to be flattened to form nanosheets or dense particles with lamellar textures.

[0038] Example 3 Thermoelectric performance test of CsAg5Te3 thermoelectric block

[0039] The thermoelectric performance of thermoelectric materials depends mainly on their thermoelectric figure of merit (zT = S 2 σT / к, where S, σ, T and к are Seebeck coefficient, electrical conductivity, absolute temperature and thermal conductivity respectively). The higher the zT value, the better the thermoelectric performance of the material. In order to verify the thermoelectric performance of the CsAg5Te3 thermoelectric material prepared by the present invention, the surface of the dense CsAg5Te3 thermoelectric block obtained by spark plasma sintering was polished and smoothed, and the relationship between its thermal transport performance and temperature was tested. The results are as follows: Figure 6 shown. Figure 6 (a) is the relationship between the thermal diffusion coefficient of the bulk sample and the temperature. Figure 6 (b) is the relationship between the thermal conductivity of the bulk sample and the temperature (the short lines at each measurement point are error bars). The thermal conductivity of the bulk 2 sample is the lowest, and its minimum thermal conductivity is 0.24 Wm at 675 K. -1 K -1 .

[0040] The block 2 sample with the lowest thermal conductivity was selected and polished into a disc with a diameter of 12.7 mm and a thickness of 1.7 mm for electrical transport performance testing. The results are as follows: Figure 7 shown. Figure 7 (a), (b) and (c) are the relationship between the bulk sample conductivity, Seebeck coefficient and power factor and temperature respectively (the short line at each measurement point is the error bar). It can be seen from the figure that the conductivity of the bulk sample decreases first and then increases with the increase of temperature. At 675K, the maximum conductivity is 47Scm -1 The Seebeck coefficient increases with temperature and can reach 227μVK at 675K. -1 The highest power factor was obtained at 675K, which was 2.4μWcm -1 K -2 .

[0041] The relationship between the thermoelectric figure of merit zT of CsAg5Te3 thermoelectric block 2 and temperature is as follows Figure 8 As shown in a, the zT value of the bulk sample is the highest at 675K, which is 0.7, indicating that the combination of fast and efficient microwave method and spark plasma sintering technology can also obtain thermoelectric bulk with excellent thermoelectric performance. Figure 8 b is the thermoelectric figure of merit of the literature (Angew.Chem.Int.Ed.2016,55,1-7). It can be seen that the thermoelectric performance of the thermoelectric block prepared in this experiment is still somewhat different from the literature value. However, the preparation time of CsAg5Te3 thermoelectric block by combining microwave method with spark plasma sintering technology is only 40 minutes, which can greatly shorten the preparation time and cost of thermoelectric block compared with the literature. It is believed that on the basis of this experimental process, the thermoelectric performance of CsAg5Te3 can be further optimized by doping modification.

[0042] Compared with the prior art, the present invention proposes for the first time to use microwave solvent thermal method to prepare CsAg5Te3 nanopowder. The reaction time only takes 30 minutes. The prepared CsAg5Te3 thermoelectric powder has a nanofiber structure, which realizes the controllable preparation of the microstructure of complex multi-component thermoelectric materials. Subsequently, the prepared fibrous CsAg5Te3 nanopowder can be sintered into a dense block within 10 minutes by using spark plasma sintering technology. The thermoelectric block presents a nanosheet or a lamellar texture structure and exhibits good thermoelectric performance. The present invention combines microwave solvent thermal method with spark plasma sintering technology. It only takes 40 minutes to prepare a dense CsAg5Te3 thermoelectric block, which greatly shortens the preparation time and provides a new idea for the rapid preparation of low-dimensional complex multi-component thermoelectric blocks.

[0043] The above embodiments are only preferred embodiments of the present invention and are not intended to limit the scope of implementation of the present invention. Those skilled in the art can make several improvements and substitutions based on the technical solution of the present invention without making any creative efforts. These improvements and substitutions all fall within the protection scope of the present invention.

Claims

1. A method for preparing high-purity fibrous CsAg5Te3 nano-thermoelectric powder, characterized in that: The method comprises the following steps: weighing CsNO3, AgNO3 and Na2TeO3 respectively according to the molar ratio of Cs:Ag:Te=12:5:3, dissolving them in a transparent mixed solution of ethylene glycol and polyvinyl pyrrolidone with a pH value of 9-10, and fully disturbing them at room temperature to obtain a black solution; The black solution was transferred to a Teflon high-pressure reactor, and the reactor was placed in a microwave reactor for a gradient temperature increase reaction. The gradient temperature increase reaction was first heated to 120°C at a rate of 24°C / min, kept warm for 5 minutes, and then heated to 230°C at a rate of 22°C / min, and kept warm for 15 minutes. After the reaction was completed, the dark gray product was separated and purified to obtain the high-purity fibrous CsAg5Te3 nanomaterial.

2. The method for preparing high-purity fibrous CsAg5Te3 nano-thermoelectric powder according to claim 1, characterized in that: The separation and purification method comprises: washing the reaction product with deionized water and anhydrous ethanol by centrifugation for multiple times, the centrifuge speed is 8000 rpm, placing the centrifuged product in a vacuum drying oven, and drying it at 60° C. for 8 hours.

3. The method for preparing high-purity fibrous CsAg5Te3 nano-thermoelectric powder according to claim 1, characterized in that: The dosage ratio of PVP to ethylene glycol is 0.8g:50ml.

4. The method for preparing high-purity fibrous CsAg5Te3 nano-thermoelectric powder according to claim 1, characterized in that: The transparent mixed solution of ethylene glycol and polyvinyl pyrrolidone is adjusted to the pH value with NaOH.

5. A method for preparing a thermoelectric block, characterized in that: The method comprises the following steps: plasma sintering the high-purity fibrous CsAg5Te3 nanopowder prepared according to the method described in any one of claims 1 to 4 at an axial pressure of 40 to 60 MPa and 400 to 500° C. for 10 minutes.

6. The method for preparing a thermoelectric block according to claim 5, characterized in that: The plasma sintering temperature is 450°C and the axial pressure is 50 MPa.

Citation Information

Patent Citations

  • Preparation method of arsenic selenide

    CN106006573A

  • Chalcogenide-based thermoelectric material and preparation method thereof

    CN115124006A